2017
DOI: 10.1186/s13075-017-1323-z
|View full text |Cite
|
Sign up to set email alerts
|

Lymphatic delivery of etanercept via nanotopography improves response to collagen-induced arthritis

Abstract: BackgroundEvidence suggests lymphatic function mediates local rheumatoid arthritis (RA) flares. Yet biologics that target the immune system are dosed systemically via the subcutaneous (SC) administration route, thereby inefficiently reaching local lymphatic compartments. Nanotopography has previously been shown to disrupt tight cellular junctions, potentially enhancing local lymphatic delivery and potentially improving overall therapeutic efficacy.MethodWe first characterized nanotopography (SOFUSA™) delivery … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 37 publications
0
17
0
Order By: Relevance
“…The ability to clinically evaluate lymphatic function in "point-of-care" studies could accelerate more effective strategies to treat these diseases. For example, we recently used NIRF-LI techniques to demonstrate the lymphatic delivery of a TNF inhibitor to restore contractile lymphatic function in an animal model of rheumatoid arthritis [118] and of a checkpoint blockade inhibitor to more effectively suppress primary tumor growth and arrest metastasis than from systemic administration [142]. The ability to develop more effective treatments for chronic conditions requires the ability to visualize the function and anatomy of the lymphatics in disease progression and in response to treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The ability to clinically evaluate lymphatic function in "point-of-care" studies could accelerate more effective strategies to treat these diseases. For example, we recently used NIRF-LI techniques to demonstrate the lymphatic delivery of a TNF inhibitor to restore contractile lymphatic function in an animal model of rheumatoid arthritis [118] and of a checkpoint blockade inhibitor to more effectively suppress primary tumor growth and arrest metastasis than from systemic administration [142]. The ability to develop more effective treatments for chronic conditions requires the ability to visualize the function and anatomy of the lymphatics in disease progression and in response to treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Lymphatic dysfunction has also been linked to rheumatoid arthritis [116][117][118][119], with LE a known comorbidity [120] and dermal backflow evident on lymphoscintigraphy [121]. Other inflammatory disorders are also associated with LE [122,123], suggesting that, again, the pro-inflammatory state is associated with lymphatic dysfunction.…”
Section: Inflammatory/rheumatological Diseasesmentioning
confidence: 99%
“…14,15 Initial trials assessed dose levels between 9 and 300 µg and revealed that the first administration induced symptoms similar to those associated with gluten exposure in CeD. 14,15 Initial trials assessed dose levels between 9 and 300 µg and revealed that the first administration induced symptoms similar to those associated with gluten exposure in CeD.…”
Section: Introductionmentioning
confidence: 99%
“…Prior Nexvax2 clinical studies in HLA-DQ2.5+ patients used intradermal administration with the assumption that exposure to cutaneous antigen-presenting cells (eg dendritic or Langerhans cells), and subsequent transit via regional lymphatics, might be important in inducing nonresponsiveness (and potentially tolerance). 14,15 Initial trials assessed dose levels between 9 and 300 µg and revealed that the first administration induced symptoms similar to those associated with gluten exposure in CeD. These were accompanied by an underlying cytokine response, characterised by pronounced increases in serum interleukin-2 within 2 hours of dosing.…”
Section: Introductionmentioning
confidence: 99%
“…Methods to stimulate drainage in the CSF drainage pathways could include pneumatic compression devices (Gutierrez et al, 2019) or manual lymphatic drainage techniques. While pro-inflammatory cytokines inhibit lymphatic function and drainage (Aldrich & Sevick-Muraca, 2013;Aldrich et al, 2017;Scallan, Zawieja, Castorena-Gonzalez, & Davis, 2016), till date there are limited studies on how to pharmacologically stimulate lymphatic drainage, particularly those draining the intracranial space. Finally, while mucosal injection into the palatine tonsils may provide convenient access to the drainage pathway shared by CSF outflow, it remains to be validated as a robust diagnostic.…”
Section: Discussionmentioning
confidence: 99%